2015
DOI: 10.1177/0739986315588917
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology and Familial Factors as Predictors of Latina/o Students’ Psychological Grit

Abstract: Positive psychology is a useful framework to understand Latina/o students' experiences. In the current study, we examined how presence of meaning in life, search for meaning in life, hope, and family importance influenced 128 Latina/o college students' psychological grit. We used the Meaning in Life Questionnaire (MLQ), Subjective Happiness Scale, Hope Scale, Pan-Hispanic Familism Scale, and Short Grit Scale to measure the aforementioned factors. Using multiple regression analysis, findings indicated that hope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 51 publications
2
80
0
1
Order By: Relevance
“…Dixson et al () found in a sample of 609 academically gifted adolescents that hope and the effort subscale of grit (i.e., one's thoughts about their work ethic) were moderately associated ( r = 0.48, p < .003). Similarly, Vela, Lu, Lenz, and Hinojosa () reported that hope was a meaningful predictor of grit after controlling for family support, subjective happiness, search for meaning, and presence of meaning in a sample of 128 college students ( β = .410, p < .01).…”
Section: Introductionmentioning
confidence: 94%
“…Dixson et al () found in a sample of 609 academically gifted adolescents that hope and the effort subscale of grit (i.e., one's thoughts about their work ethic) were moderately associated ( r = 0.48, p < .003). Similarly, Vela, Lu, Lenz, and Hinojosa () reported that hope was a meaningful predictor of grit after controlling for family support, subjective happiness, search for meaning, and presence of meaning in a sample of 128 college students ( β = .410, p < .01).…”
Section: Introductionmentioning
confidence: 94%
“…Such strategies are thought to be principally important when individuals are facing impediments to their continued engagement and effort in certain tasks (Wolters 1998(Wolters , 2003. In line with this, and recent studies (Datu 2017;Hill et al 2016;Mueller et al 2017;Vela et al 2015), we conceptualise grit as a malleable construct, as opposed to a static personality trait. We propose that grit should be conceptualised within a cognitive-affective framework of self-regulation in order to identify and understand grit-enhancing strategies.…”
Section: Grit Within a Self-regulatory Frameworkmentioning
confidence: 60%
“…According to Sears and Kraus (), hope provides a sense of goal‐directed determination and ability to generate plans to achieve goals. Researchers found that hope is related to high school and college students’ psychological grit (Vela, Lu, Lenz, & Hinojosa, ), meaning in life (Vela, Lerma, et al, ), academic performance (Snyder et al, ), and mental health (Marques, Pais‐Ribeiro, & Lopez, ). Finally, Larsen and Stege () posited that hope is related to psychological and physical health, academic performance, and positive life outcomes.…”
Section: Positive Psychology Factorsmentioning
confidence: 99%
“…In summary, gratitude, meaning in life, and hope have been theoretically and empirically linked in previous studies in positive psychology (e .g ., Vela, Lu, et al ., 2015) . From a positive psychology perspective, students who have high levels of gratitude and appreciation for their past might also have higher levels of meaning in life as well as hope for their future .…”
Section: Positive Psychology Factorsmentioning
confidence: 99%
See 1 more Smart Citation